The Cultural and Gender Politics of Enunciation Locating the Singer-Songwriter within and beyond Male Anglo-American Contexts. (3rd February 2015) - Wheeler, Duncan; O'Brien, Lucy
Abstract : This conversation between Lucy O'Brien and Duncan Wheeler seeks to establish a dialogue between musicologists and modern-language specialists to interrogate how their respective disciplinary and biographical questions might address a series of overarching themes and questions—sexism and gender-inflected ageism in the music industry; reclaiming silenced female and non Anglophone singer songwriters; the complex and frequently contradictory interrelationships between sex, art and commerce—in order to undertake a common endeavour: decentring a canon that remains disproportionately Anglo American and male.